In theory-Sharing AI's black box sounds great-But in reality it's not - Richard M Fleming; Matthew R Fleming; Tapan K Chaudhuri (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
In theory, the concept of sharing scientific information and knowledge seems safe [1]. However, in reality those who seek to obtain that knowledge are not always so pure in motive - consider Nobel's experience with dynamite (Patent # 78317) - something driven home at every meeting we present The Fleming Method for Tissue and Vascular Differentiation and Metabolism (FMTVDM) at [2], an example of which is shown in Figure 1.